The History of Human Rights in the Process Building Timor Leste as State of Law: Timor Leste State Building of Law - dos Santos, Hercus Pereira (Yayasan Meira Visi Persada, 2025)
The History of Human Rights began since the existence of human beings in which it is called natural rights and that throughout human history, these natural rights have been questioned and violated and only with the creation of the United Nations, Human Rights were formalized with the Universal Declaration of Human Rights with the main intention to respect the dignity of the human person, avoid war and all things that endanger Human Rights. Timor-Leste as a new state of the 21st century was born at a time when Human Rights are highly valued and become a sensitive subject that attracts a lot of attention from the international community, which makes Timor-Leste's struggle for independence go through the struggle for Human Rights and that has a very strong echo and has managed to attract strong support in the world for the right to self-determination. Therefore, we can say that the struggle for independence in Timor-Leste is also a struggle for Human Rights. Aware of the importance of Human Rights in the world and in the lives of people, since the beginning of independence and in the process of building the rule of law, Timor-Leste has already ratified the international human rights treaties to ensure that independent Timor-Leste values, respects and avoids any type of human rights violations. Timor-Leste must not repeat the human rights violations of the past but must promote the protection and enhancement of human rights for all.